DEVELOPMENT OF AUDIO VISUAL MEDIA ON PROBLEM BASED LEARNING TO INCREASE COGNITIVE LEARNING OUTCOMES AT CLASS X SMA NEGERI 7 PURWOREJO - Adjie Kurniawan , Jumadi (Universitas negeri Yogyakarta, 2018)
Abstrak Penelitian ini bertujuan untuk: (1) menghasilkan produk media audio visual fisika yang layak untuk digunakan dalam pembelajaran di kelas (2) mengetahui peningkatan hasil belajar peserta didik setelah diimplementasikan media audio visual dalam pembelajaran Problem Based Learning di kelas, dan (3) mengetahui perbedaan peningkatan hasil belajar kognitif peserta didik antara kelas yang menggunakan media audio visual dengan kelas konvensional. Kata Kunci: media audio visual, problem based learning, hasil belajar kognitif Abstract This study aimed: (1) to produce the properness of audio visual media based on the video in physics Problem Based Learning, (2) to know the increasing of cognitive learning outcomes whose taught using audio visual media on Problem Based Learning, (3) to know the difference of an increase of learning outcomes whose taught using audio visual media and comparing these results with the conventional learning media.